The Social Protection Floor and the 'New' social investment policies in Japan and South Korea. (December 2014) - Peng, Ito
Japan and South Korea have always taken what may be called a social investment approach to their social and economic development policies. They were able to achieve a high level of economic growth, in part, because of their targeted social spending that supported and protected the productive sectors of the society. Since the 1990s, however, there has been a marked shift in the targets of social investment, from predominantly skilled, male, industrial core workers to more peripheral, marginalized, and vulnerable population groups, such as women, children, and the elderly. Moreover, this new policy focus is now increasingly put forward from the perspective of inclusive welfare and the discourse of social inclusion, thus breaking from the earlier productivist thinking. Indeed, recent social investment policy debates in the two countries are often framed in terms of intergenerational equity, social and economic sustainability, and economic democracy. What are these 'new social investments', and why the shifts? This article looks at the new social investment policies in Japan and South Korea to understand factors behind the changes, and assess how 'new' are these new social investments.